2022
DOI: 10.3390/epigenomes6040031
|View full text |Cite
|
Sign up to set email alerts
|

Population Epigenetics: The Extent of DNA Methylation Variation in Wild Animal Populations

Abstract: Population epigenetics explores the extent of epigenetic variation and its dynamics in natural populations encountering changing environmental conditions. In contrast to population genetics, the basic concepts of this field are still in their early stages, especially in animal populations. Epigenetic variation may play a crucial role in phenotypic plasticity and local adaptation as it can be affected by the environment, it is likely to have higher spontaneous mutation rate than nucleotide sequences do, and it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 147 publications
0
12
0
Order By: Relevance
“…Significant associations between genetic or epigenetic variation and environmental parameters (e.g., temperature or salinity) have previously been reported in various invertebrates ( 25 29 ), with a significant correlation between genetic and epigenetic variation found in 6 of 14 studies reviewed ( 30 ). MethQTL mapping revealed that the fraction of epigenetic variation associated with DNA sequence variation ( 26 , 28 , 31 ) is highly variable, ranging from 2% in the threespine stickleback ( Gasterosteus aculeatus ) ( 31 ), 3% in the Olympia oyster ( Ostrea lurida ) ( 28 ), 19% in Ciona intestinalis ( 26 ), 70% in human ( Homo sapiens ) ( 32 , 33 ), and 88% in this study.…”
Section: Discussionmentioning
confidence: 91%
“…Significant associations between genetic or epigenetic variation and environmental parameters (e.g., temperature or salinity) have previously been reported in various invertebrates ( 25 29 ), with a significant correlation between genetic and epigenetic variation found in 6 of 14 studies reviewed ( 30 ). MethQTL mapping revealed that the fraction of epigenetic variation associated with DNA sequence variation ( 26 , 28 , 31 ) is highly variable, ranging from 2% in the threespine stickleback ( Gasterosteus aculeatus ) ( 31 ), 3% in the Olympia oyster ( Ostrea lurida ) ( 28 ), 19% in Ciona intestinalis ( 26 ), 70% in human ( Homo sapiens ) ( 32 , 33 ), and 88% in this study.…”
Section: Discussionmentioning
confidence: 91%
“…Significant associations between genetic or epigenetic variation and environmental parameters (e.g. temperature or salinity) have previously been reported in various invertebrates 24-28 , with significant correlation between genetic and epigenetic variation found in six of 14 studies reviewed 29 . Analyses of genetic control of epigenetic variation using methQTL have found that the fraction of epigenetic variation under direct control of DNA sequence variation 25,27 ,30 is highly variable, ranging from 2% in the threespine stickleback ( Gasterosteus aculeatus ) 30 , 3% in the Olympia oyster ( Ostrea lurida ) 27 , 19% in Ciona intestinalis 25 , 70% in human ( Homo sapiens ) 31,32 , and 88% in this study.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, most genes with outliers were associated with protein binding and catalytic activities and were involved in metabolic and growth processes (Figure S3), critical molecular functions for gene expression regulation and phenotypic diversification (Van Nostrand et al, 2020). In small, isolated populations, extensive modulation of gene expression conferring phenotypic plasticity could represent a major mechanism to counteract the loss of genetic diversity (Fulgione et al, 2023; Sherpa et al, 2023), a hypothesis that needs to be validated by whole transcriptome and epigenome data (Chapelle and Silvestre, 2022; Fulgione et al, 2023).…”
Section: Discussionmentioning
confidence: 99%